Math and Arithmetic
Education

# How do you simplify 3 2x 4y 7x 3 10x?

012 ###### 2015-02-22 11:29:38

Unfortunately, the browser used by Answers.com for posting questions is incapable of accepting mathematical symbols. This means that we cannot see the mathematically critical parts of the question. We are, therefore unable to determine what exactly the question is about and so cannot give a proper answer to your question.

🦃
0
🤨
0
😮
0
😂
0

## Related Questions 7x - 4y + x = 8x - 4y Depending on what your teacher is looking for, I might even go a step further to simplify it to 4(2x-y). 3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y 10x - 3 - 2x = 4 7x - 3 = 4 7x = 7 x = 1  According to the distributive property, 7x(4y + 4) - 8(4y + 4) = (7x - 8)(4y + 4). Is this question true or false?&gt; it means to put together the terms that have the same variable. so if you had the equation: 2x+4y+5x it would simplify to 7x+4y because you would combine to the two x-variables. 7x + 13 = 2x + 3 First, subtract 3 from both sides.7x + 13 - 3 = 2x + 3 - 3Simplify both sides.7x + 10 = 2xNow, subtract 2x from both sides.7x - 2x + 10 = 2x - 2xSimplify again.5x + 10 = 0Finally, subtract 10 from both sides, simplify, and divide both sides by 5.5x + 10 - 10 = 0 - 105x = -10x = -2So the answer is x = -2. (14x^3 - 10x^2) = 2x^2(7x - 5) 63x - 45 = 9(7x - 5) 14x^3 - 10x^2 + 63x - 45 = (2x^2 + 9)(7x - 5) 10x&sup2; - 7x - 12 = (5x + 4)(2x - 3)  18 + 7x - 12 + 5x = ?18 - 12+ 7x - 5x = ?6 + 2x = ? To function form. - 7X - 4Y = 16 - 4Y = 7X + 16 Y = - 7/4X - 4 ------------------------ The slope is, - 7/4 --------  10x + 5 which is also equal to 5(2x + 1) simplify it, 7x-12=x+2+2x-3x 7x=2+12+3x-3x 7x=14 x=2 7x+4y = 39 2x+4y = 14 Subtract the equations in order to eliminate y: 5x = 25 Divide both sides by 5 to find the value of x: x = 5 Substitute the value of x into the original equations to find the value of y: Therefore: x = 5 and y = 1 the simplest form of 5x + 3y +2x - 6y is 7x-3y 2x2 + 7x - 15 = 02x2 + 10x - 3x - 15 = 0(2x2 - 3x) + (10x - 15) = 0x(2x - 3) + 5(2x - 3) = 0(2x - 3)(x + 5) = 0(2x - 3) = 0 or (x + 5) = 0x = 3/2 or x = -5 12 - 3x = 24 - 10x so 7x = 12 making x = 12/7 or one and five-sevenths. The greatest common factor in the two terms is [ 4y ].The factored form of the expression is4y (y + 7x) "Combine like terms" means you have to join 2 or more similar terms into one term. Doing this can simplify an equation or expression. For example, 10x+3+7x 10x and 7x are like terms. Therefore, the coefficients 10 and 7 can be added together. So: 10x+3+7x=17x+3   7x-4020+3x= 7x+-4020+3x= 7x+3x+-4020= 10x+-4020= 10x-4020 Answers to pick: -2x - y = 4 2x + y = -2 -8x + 4y = -16 -4x + 2y = -8 -x - 2y = 6 -7x + 4y = 16 2x + 3y = 6 3x + 2y = 4

###### Math and ArithmeticFactoring and MultiplesAlgebraSchool Subjects Copyright © 2020 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.